POTENSI USAHA DAN EFISIENSI EKONOMI RAKYAT DI KABUPATEN OGAN KOMERING ULU TIMUR - Zulkarnain Ishak; Imam Asngari (Department of Development Economics, Universitas Sriwijaya, 2009)
The objectives of the study are to analyze economic potential and efficiency on small scale economic or â€œekonomi rakyatâ€ of Ogan Komering Ulu Timur (OKU Timur) Municipality. The primary data by used of this research, and the people economies analysis by using efficiency and production approaches. The result of the research shows that â€œekonomi rakyatâ€ in OKU Timur has biggest potential based on production approach, sales, profitability and efficiency. In sector of mining, hotels and restaurant have highest efficient and feasible to developed, sector of industry, and paddy production, while wallet nest, Pedigree Fowl and Domestic Hens are also efficient and feasible. Meanwhile, the efficiency while do the opposites of its input production from out-of local area, such as tradable goods and car services is not efficient. Key words: economic potential, small scale economy, ekonomi rakyat, production, input, cost, efficiency and B/C ratio.